Pengaruh Kualitas Produk, Daya Tarik Iklan, dan Harga terhadap Keputusan Pembelian: Studi pada Konsumen Jasa Cetak di Surabaya - Pratama, Hadyan Taris; Artanti, Yessy (Inspirasi Nusantara, 2023)
In the era of intense business competition, particularly in the printing industry in Indonesia, especially in Surabaya, a profound understanding of the factors influencing purchasing decisions becomes crucial. This research, titled Analysis of the Influence of Product Quality, Advertising Appeal, and Price on Purchase Decisions, aims to present a holistic overview of the roles of product quality, advertising appeal, and price in shaping purchasing preferences in the printing service sector in the city of Surabaya. Using multiple linear regression analysis, this study details findings derived from carefully collected data from 110 respondents selected based on research needs. The results provide significant insights into the dominant roles of product quality and advertising appeal in shaping consumer purchasing behavior in the offset printing market in Surabaya. Although price remains a crucial consideration, interesting findings indicate the opposite (in this context, not showing statistical significance). Thus, this research not only delves into the depth of consumer behavior in the printing service industry but also provides practical insights for industry players seeking to enhance their marketing strategies. Conclusions and recommendations from this study are expected to be valuable guidance for anyone conducting further research or companies developing more effective and responsive marketing strategies to meet consumer needs and preferences.